A mi manera ¿cómo ser guionista en un país sin industria audiovisual? - Gutierrez Mongrut, Rosa Angelica (2025)
This work describes my career and experience as a professional screenwriter over more than 25 years, during which I have led teams of writers and written for multiple productions successfully broadcast during prime time on the most important free-to-air television channels. Throughout this document, I reflect on the path I have taken to carve out a space for myself in an industry dominated by men, in a country with little to no audiovisual industry. Through the experiences I recount, I reveal an informal industry where I learned to navigate both its advantages and disadvantages in order to grow as a writer. Each job, each production, and each experience taught me something valuable that helped me progress toward a goal that was not so clear at the beginning: becoming a screenwriter. I am certain that these lessons can also be useful for aspiring screenwriters in Peru.